Evolução da receita pública: um estudo aplicado ao Município de Fortaleza – 2010 a 2021 - Silva, Maria Regilania da (2024)
The public revenues play a crucial role in municipal public management, given their distribution and allocation to finance local expenditures. In this perspective, this study aimed to survey the evolution of the public revenue of the municipality of Fortaleza from 2010 to 2021, aiming to identify the main sources of municipal public revenue. This is an exploratory and descriptive study that employs technical procedures of bibliographic and documentary research to gather knowledge on the subject and collect data for analysis. The results showed that despite Fortaleza Municipality experiencing growth in tax revenue between 2010 and 2021, it still exhibits a strong dependence on intergovernmental transfers. Additionally, the study highlights the need for improvement in fiscal efforts to make fiscal management more efficient, reducing reliance on intergovernmental transfers.